On Impatience and Policy Effectiveness - Sgherri, Silvia (IMF Working Papers; Working Paper ;, 2009)
An increasing body of evidence suggests that the behavior of the economy has changed in many fundamental ways over the last decades. In particular, greater financial deregulation, larger wealth accumulation, and better policies might have helped lower uncertainty about future income and lengthen private sectors' planning horizon. In an overlapping-generations model, in which individuals discount the future more rapidly than implied by the market rate of interest, we find indeed evidence of a falling degree of impatience, providing empirical support for this hypothesis. The degree of persistence of "windfall" shocks to disposable income also appears to have varied over time. Shifts of this kind are shown to have a key impact on the average marginal propensity to consume and on the size of policy multipliers.